Pengaruh Literasi Keuangan terhadap Kinerja Usaha Mikro Kecil (UMK) di Kecamatan Berastagi - Barus, Epi Pransiska Br; Siahaan, Audrey M.; Sihombing, Halomoan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to find out what influence Financial Literacy has on the Performance of Micro and Small Enterprises in Kabanjahe District. The independent variable is Financial Literacy and the dependent variable is Micro and Small Business Performance. The research method used is primary data collection techniques in the form of questionnaires. The sampling method used in this research is Conveience Sampling. With a total sample of 35 respondents. Data processing uses SPSS version 26 tools. Tests used in this research include descriptive statistical analysis, validity and reliability tests, normality tests, simple linear regression, and partial significance tests (t tests). The results of this research show that Financial Literacy (X) has a positive, significant effect on the Performance of Micro and Small Enterprises (Y) in Berastagi District. Based on the results of the t test, the Financial Literacy variable has an effect on the performance of Micro and Small Enterprises in Berastagi District by 0.040 (0.040<0.05).